jagr2713
  • jagr2713
f(7)= -x2+3x-6 i got 64 but its says its wrong
Mathematics
  • Stacey Warren - Expert brainly.com
Hey! We 've verified this expert answer for you, click below to unlock the details :)
SOLVED
At vero eos et accusamus et iusto odio dignissimos ducimus qui blanditiis praesentium voluptatum deleniti atque corrupti quos dolores et quas molestias excepturi sint occaecati cupiditate non provident, similique sunt in culpa qui officia deserunt mollitia animi, id est laborum et dolorum fuga. Et harum quidem rerum facilis est et expedita distinctio. Nam libero tempore, cum soluta nobis est eligendi optio cumque nihil impedit quo minus id quod maxime placeat facere possimus, omnis voluptas assumenda est, omnis dolor repellendus. Itaque earum rerum hic tenetur a sapiente delectus, ut aut reiciendis voluptatibus maiores alias consequatur aut perferendis doloribus asperiores repellat.
jamiebookeater
  • jamiebookeater
I got my questions answered at brainly.com in under 10 minutes. Go to brainly.com now for free help!
freckles
  • freckles
\[f(x)=-x^2+3x-6 \\ \text{ and you are asked to evaluate } f(7) ?\]
freckles
  • freckles
by the way -x^2 means -1*x*x
freckles
  • freckles
-x^2 is not the same as (-x)^2

Looking for something else?

Not the answer you are looking for? Search for more explanations.

More answers

freckles
  • freckles
which looks like what you did
jagr2713
  • jagr2713
oh it does 0_0 i put -7^2+3(7)-6
freckles
  • freckles
which is -49+21-6
jagr2713
  • jagr2713
wait for mines i got 49+21-6 = 64
freckles
  • freckles
as said you did (-x)^2
freckles
  • freckles
but the question says -x^2
freckles
  • freckles
-x^2 is -1*x*x not (-x)*(-x)
freckles
  • freckles
\[-x^2=-1 \cdot x^2 \text{ or } -1 \cdot x \cdot x \\ \text{ where as } (-x)^2 =(-x) \cdot (-x)=x \cdot x =x^2 \text{ which is what you did } \\ \text{ and } -x^2 \text{ does not equal } (-x)^2 \]
jagr2713
  • jagr2713
so can u give it to me when you first plug it in
jagr2713
  • jagr2713
so its -7^2 ?
freckles
  • freckles
yes not (-7)^2
freckles
  • freckles
the exponent is on the x not the - and the x
freckles
  • freckles
\[g(x)=-x^2 \\ g(7)=-7^2=-(7^2)=-(7 \cdot 7)=-(49)=-49\]
jagr2713
  • jagr2713
so thats -49?
freckles
  • freckles
if you had \[h(x)=(-x)^2 \\ \text{ then } h(7)=(-7)^2=(-7 \cdot -7)=49\]
jagr2713
  • jagr2713
OHOHOHOHHOHO i seeeeeee
jagr2713
  • jagr2713
so if its for example f(8) we put -8^2 so 8*8=64 and the negative sign is after so -64
freckles
  • freckles
yes -8^2 means -(8*8)=-(64)=-64
freckles
  • freckles
where as (-8)^2=(-8)*(-8)=64
jagr2713
  • jagr2713
so the answer is *34?
freckles
  • freckles
do you see difference between -x^2 and (-x)^2 ?
jagr2713
  • jagr2713
-34?
freckles
  • freckles
\[-7^2+3(7)-6 \\ -49+21-6 \\ -(49-21)-6 \\ -(28)-6 \\ -28-6 \\ -34\] yes
jagr2713
  • jagr2713
OMG your the best thanks!!!!!
freckles
  • freckles
np

Looking for something else?

Not the answer you are looking for? Search for more explanations.